1995
DOI: 10.2508/chikusan.66.27
|View full text |Cite
|
Sign up to set email alerts
|

Does Feed-Restriction Refeeding Program Improve Growth Characteristics and Body Composition of Broiler Chickens¿

Abstract: An experiment was conducted to study the effect of feed-restriciton refeeding program on growth characteristics, hepatic lipogenic enzymes activities, lipid composition in liver and serum, abdominal fat weight and body composition in female broilers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The present study agreed with the observation of Ballay et al (1992) who found that the age when the restriction was started (1, 7 or 13 days of age) had no effect on abdominal fat of sexed broilers. Our results (Experiment 1) also agreed with the observation of Santoso et al (1995b) who found that duration of restriction did not affect abdominal fat in sexed broilers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study agreed with the observation of Ballay et al (1992) who found that the age when the restriction was started (1, 7 or 13 days of age) had no effect on abdominal fat of sexed broilers. Our results (Experiment 1) also agreed with the observation of Santoso et al (1995b) who found that duration of restriction did not affect abdominal fat in sexed broilers.…”
Section: Discussionsupporting
confidence: 92%
“…They postulated that since lipogenesis in poultry occurs primarily in the liver, with unused fatty acids stored as trilgyceride in adipose tissue, lipid content in the liver would not be expected to be different in broilers exposed to different feeding treatments. However, this postulation was not wholly true, since Santoso et al (1993aSantoso et al ( , 1995b found that early feed restriction changed hepatic triglyceride content.…”
Section: Discussionmentioning
confidence: 99%
“…In the rehabilitation period, chicks grow more rapidly to compensate for lost growth due to dietary restrictions (Summers et al, 1990;Bowes and Julian, 1998). Following the restricted feed program, the birds are fed a diet of high quality resulting in faster growth compared to the natural growth of the animal's age which is probably due to increased nutrient utilization; this phenomenon is called 'compensatory growth' (Pinchasov et al, 1993;Zubair and Leeson, 1994;Acar et al, 1995;Santoso et al, 1995;De Silva and Kalubowila, 2012;Butzen et al, 2013). Some researchers consider use of restricted feed programs and lighting programs as the key to reduce maintenance costs and to prevent metabolic abnormalities in modern strains (Jahanian et al, 1990;Fontana et al, 1992;Donald et al, 2000).…”
mentioning
confidence: 99%
“…Effect of restricted feeding on the deposition of fat in broiler chickens has so far been investigated extensively to reduce abdominal fat and body fat without loss of growth performance of broiler, summarized as a review by LEENSTRA (1986). There are a number of studies concerned with the fat deposition under the ad libitum feeding in broiler chickens which had been restricted the food intake for short period during the earlier stage of growth (PLAVNIK and HURWITZ, 1988, 1990, 1991YU et al, 1990;CABEL and WALDROUP,1990;BALLAY,1992;SANTOSO et al, 1993SANTOSO et al, , 1995. However, few investigations have been carried out to determine the relationship between the growth of muscle and fat deposition in broiler chickens which have been restricted the feed intake for considerably long time.…”
Section: Introductionmentioning
confidence: 99%